2021
DOI: 10.3390/s21186310
|View full text |Cite
|
Sign up to set email alerts
|

A Blockchain-IoT Platform for the Smart Pallet Pooling Management

Abstract: Pallet management as a backbone of logistics and supply chain activities is essential to supply chain parties, while a number of regulations, standards and operational constraints are considered in daily operations. In recent years, pallet pooling has been unconventionally advocated to manage pallets in a closed-loop system to enhance the sustainability and operational effectiveness, but pitfalls in terms of service reliability, quality compliance and pallet limitation when using a single service provider may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…Finally, 12% of the publications related to SCM and BCT are under the business/management/accounting field, followed by 5% under the environmental sciences area and 1% under agricultural and biological sciences. There are strong ties between BCT and IoT, and that is aligned with the recent research pointing out the future era of (BIoT) [37,38]…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Finally, 12% of the publications related to SCM and BCT are under the business/management/accounting field, followed by 5% under the environmental sciences area and 1% under agricultural and biological sciences. There are strong ties between BCT and IoT, and that is aligned with the recent research pointing out the future era of (BIoT) [37,38]…”
Section: Discussionsupporting
confidence: 62%
“…They found that the suggested system positively impacts the overall quality of the pooling, increases end-user trust and satisfaction level, facilitates traceability, and minimizes errors. Moreover, this integration leverages cyber security by minimizing system vulnerabilities [38].…”
mentioning
confidence: 99%
“…• Solution based on peer-to-peer decentralized technology, typically a blockchain solution. There are many recent examples, including [61][62][63][64][65][66], and the number of solutions is growing quickly. Decentralization removes the requirement of trusting the cloud provider.…”
Section: Cloud and Blockchain In Iot Securitymentioning
confidence: 99%
“…The operation of an intelligent forklift is quite straightforward; typically, it inserts and picks up pallets at one preset area before travelling to another to dump them off, accomplishing a full pallet transfer procedure. However, implementing such a straightforward approach presents numerous specific difficulties: Existing methods are more costly for determining whether a pallet is available at a certain location, while the recognition rate is low and also susceptible to interference by environmental factors [ 4 ]. When the intelligent forklift inserts the pallet, there are problems of high implementation cost [ 5 ], low algorithm robustness and insufficient accuracy for the calculation of the relative position between the pallet and the forklift.…”
Section: Introductionmentioning
confidence: 99%
“…Existing methods are more costly for determining whether a pallet is available at a certain location, while the recognition rate is low and also susceptible to interference by environmental factors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%